Pembeajaran Keterampilan Berbicara Berbasis Daring (Stui Inovasi Pendidik di TK Aisyiyah Bustanul Athfal 5 Medan di Masa Wabah Covid 19) - Hilda Zahra Lubis; Ramisah Br. Ginting; She Ukurta Br. Sitepu; Dini Mahyarani (Hikmah, 2020)
This study aims to analyze the kinds of online-based speaking skills learning, (2) the various forms of cooperation between parents and teachers in learning children's speaking skills, (3) obstacles in the application of online-based children's speaking skills learning. The research method used is a qualitative method, with a descriptive study approach. The results showed that the variety of learning speaking skills based online was as follows: (1) Learning to tell experiences on holidays, (2) listening to and retelling fairy tales or stories, (3) telling stories about dreams and future the child wants to achieve. The types of collaboration between parents and teachers in learning children's speaking skills are as follows, Intense communication about children's problems, Assisting children in learning from beginning to end of meeting hours. Constraints in the application of online-based children's speaking skills learning are as follows: (1) lack of parental assistance, (2) Internet package constraints, (3) poor internet network, (3) less enthusiastic learning activities.